2020
DOI: 10.1007/s10815-020-01934-z
|View full text |Cite
|
Sign up to set email alerts
|

A freeze-all strategy does not increase live birth rates in women of advanced reproductive age

Abstract: Research question Does a freeze-all strategy improve live birth rates in women of different age groups? Design Retrospective cohort study of 1882 first embryo transfer cycles, performed between January 2013 and December 2015. Reproductive outcomes between fresh (FRESH) or frozen (FROZEN) embryo transfers were compared in patients stratified by age: < 35, between 35 and 38, or > 38 years. Student's t test for independent samples and χ 2 analyses were used as needed. A multivariable logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…These tendencies were evident in patients younger than 38 years old, whereas no such differences were observed in those aged over 39 years. Similar results have been reported in a previous study (17).…”
Section: Discussionsupporting
confidence: 93%
“…These tendencies were evident in patients younger than 38 years old, whereas no such differences were observed in those aged over 39 years. Similar results have been reported in a previous study (17).…”
Section: Discussionsupporting
confidence: 93%
“…Yet another retrospective study in a general infertile population was recently published since completion of here presented manuscript, though this time based on patient age. Once again, the study demonstrated outcome bene ts for an all-freeze strategy in only good-prognosis patients, this time de ned as women under age 35 [24]. That age group in a large majority, however, represent exactly the approximately 15% of good-prognosis patients in an average IVF patient population, with another 15% being poor-and 70% average-prognosis patients [13].…”
Section: Limitations and Conclusionmentioning
confidence: 76%
“…Multivariable logistic regression analysis was performed to explore the associations of storage duration with ectopic pregnancy and miscarriage. The potential confounding factors were adjusted in models according to previous studies, including maternal age at oocyte pick-up (OPU) (continuous), body mass index (BMI) (continuous), reproductive center, infertility type (primary or secondary), cause of infertility (female factors, male factors, both, or unexplained), duration of infertility (continuous), endometrium preparation regimen (natural, programmed, or ovarian stimulation), oocyte yield (continuous), and the stage (cleavage or blastocyst), quality (high-quality or not), and number (continuous) of transferred embryos ( 19 , 30 , 31 ). Tests for overall linear trends were conducted using the median concentration in each group as a continuous variable.…”
Section: Methodsmentioning
confidence: 99%